Analyzing English Teachers' Teaching Module in Adressing Students' Learning Needs for Inclusive Learning - Jumraini Jumadil (Universitas Muhammadiyah Makassar, 2025)
This study aimed to analyze teaching modules used by the English teacher in addressing students’ learning needs to provide Inclusive learning in the classroom. Assessing elements and strategies used by the teacher in designing the module and how teaching modules support teachers in facing the diversity of students’ learning needs in the class, as well as the challenges and successes during the implementation. Using qualitative research, this study involved document analysis, interviews, and classroom observation to identify the elements in the lesson plan that contribute to inclusive learning effectiveness. The finding suggested the use of interactive media and sources in teaching an inclusive class in order the teachings are able to cover students’ diverse needs. Through the modules, it can be observed that teachers implemented various strategies, including scaffolding techniques, differentiated tasks, collaborative learning, incorporating technology, and culturally responsive teaching. The findings also highlighted potential challenges in facing diverse classes, such as a lack of sources, time constraints, and a lack of professional development for teachers. The findings were expected to contribute to inclusive and adaptive teaching modules to cover the students’ diversity.